Optimized Sawhorse Waveform for the Measurement of Oxytocin Release in Zebrafish - Jarosova, Romana; Douglass, Adam D; Johnson, Michael A (Analytical chemistry, 2022)
Oxytocin is a nonapeptide hormone involved in numerous physiological functions. Real-time electrochemical measurements of oxytocin in living tissue are challenging due to electrode fouling and the large potentials needed to oxidize the tyrosine residue. Here, we used fast-scan cyclic voltammetry at carbon-fiber microelectrodes and flow injection analysis to optimize a waveform for the measurement of oxytocin. This optimized waveform employed an accumulation potential of -0.6 V, multiple scan rates, and a 3 ms holding potential at a positive, oxidizing potential of +1.4 V before linearly scanning the potential back to -0.6 V (versus Ag/AgCl). We obtained a limit of quantitation of 0.34 ± 0.02 μM, and our electrodes did not foul upon multiple injections. Moreover, to demonstrate the utility of our method, we measured the release of oxytocin, evoked by light application and mechanical perturbation, in whole brains from genetically engineered adult zebrafish that express channelrhodopsin-2 selectively on oxytocinergic neurons. Collectively, this work expands the toolkit for the measurement of peptides in living tissue preparations.
Keywords: Neurons; karbonové vlákno; neurony; oxytocin; Animals; Zebrafish; zvířata; dánio pruhované; Microelectrodes; Oxytocin; Carbon Fiber; mikroelektrody